iProperty profiting from ideas in an age of global innovation - Barrett, William A., 1966- (John Wiley & Sons, 2008)
"In today's turbulent global economy, companies establish competitive advantage by creating the most exciting ideas and taking them to market. To sustain this competitive advantage and thrive long term, innovative companies must use intellectual property to protect their valuable ideas. iProperty explores the intellectual property strategies and tactics used by successful companies to protect ideas. Avoiding these extremes, iProperty emphasizes the concrete details involved in actual implementation and provides executives, managers and attorneys with practical advice for developing and executing a strategic intellectual property plan that will yield a measurable return on investment."--Pub. description